Analisis Studi Literatur Pemahaman Mahasiswa Tentang Algoritma Pemrograman - Syofiah Sinaga; Yahfizham Yahfizham (STIKes Ibnu Sina Ajibarang, 2024)
Students’ understanding can be through various learning concepts. In this research, the author raises the title of studants’ understanding of programming algorithms. An algorithm is procedure that is arranged in writing and sequentially and when related to programming it means sequential procedures and a structure for creating a program. The method used I this research is literature study. The author collects data or reference sources regarding students’ understanding of programming algorithms. After collecting the data, the author will analyze the references that have been collected. Analysis of this literature study will be effective in increasing the author’s and reader’s understanding of programming algorithms